PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI PENDIDIK PADA PROGRAM PENDIDIKAN GURU PENGGERAK DI SEKOLAH DASAR - Nuryati Nuryati (Jurnal Lingkar Mutu Pendidikan, 2023)
The guru penggerak (teacher mover) program which has been soundly communicated from the Ministry of Education and Culture to source learning leaders that can improve the quality or benchmark of the education in Indonesia, needs principals who can motivate teachers to join this program. This program can be successful when the enrolled teachers’ motivation is improved. The force to move the teacher to join the program is from the principal as the leader in an educational institution. Principals can improve their school’s quality as innovative, reflective, independent, collaborative and students’ champion teachers as the values in a teacher mover (guru penggerak). Any obstacles and challenges that happened have to be battled with the teacher’s persistence to improve to be an learning educator. The method used for this research is qualitative research with the data compilation method from interview. Samples are taken from 11 Primary Schools chosen randomly. Principals are expected to be able to motivate teachers, so this guru penggerak (teacher mover) program can beneficially improve the education quality in Indonesia.